2017
DOI: 10.1007/s12011-017-1098-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Fluorosis on Calcium Ions and CaMKIIα, and c-fos Expression in the Rat Hippocampus

Abstract: This study investigated neurotoxicity of chronic fluorosis in the rat hippocampus. Newly weaning, male, Sprague-Dawley (SD) rats were administered 15, 30, and 60 mg/L sodium fluoride (NaF) solution (fluorine ion concentration 8.25, 16.50, and 33.00 mg/L, respectively), and tap water, for 18 months. The neurotoxicological mechanism was examined with a focus on intracellular calcium overload. Results showed that as the fluoride concentration increased, calcium ion concentration [Ca], the expression of calcium/ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…As the major isoform of CaMKII, CaMKIIα is highly sensitive to intracellular Ca 2+ levels. 11,12 Intracellular Ca 2+ plays a pivotal role in multiple physiological processes and in responding to noxious stimulation and is closely related to cell apoptosis and necrosis. 34,35 In normal physiological conditions, the concentration of Ca 2+ in the extracellular matrix is much higher than the cytoplasmic-free Ca 2+ concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the major isoform of CaMKII, CaMKIIα is highly sensitive to intracellular Ca 2+ levels. 11,12 Intracellular Ca 2+ plays a pivotal role in multiple physiological processes and in responding to noxious stimulation and is closely related to cell apoptosis and necrosis. 34,35 In normal physiological conditions, the concentration of Ca 2+ in the extracellular matrix is much higher than the cytoplasmic-free Ca 2+ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…68 A large number of studies have shown that CaMKIIα is involved in and mediates neuronal death in cerebral ischemia and poisoning (fluorosis), which leads to damage of the nervous system. 912…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have suggested a detrimental effect of fluoride exposure on neurons however, these effects occur at dose levels outside of the expected in vivo range of ppb (Table 4 ) (Zhang et al 2008 (10–40 ppm); Lee et al 2016 (5 mM NaF; 89 ppm F − ); Inkielewicz-Stepniak et al 2012 ; 1.9 and 4.75 ppm F − ). For in vivo exposure, neuronal death or dysfunction was observed in the rat hippocampus (Basha et al 2011 ; Shashi and Kumar 2016 ; Shivarajashankara et al 2002 ; Yan et al 2016 ; Teng et al 2017 ) and neuronal shrinkage in the frontal cortex (Akinrinade et al 2015 ). In the current study, hippocampal neurons displayed a normal morphology with no evidence of neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…There was also no significant difference in the number of pyramidal neurons in the medial prefrontal cortex cells after administration of 5, 10, and 20 mg/kg b.w./day of oral NaF solution (Pulungan et al 2018). Other studies observed neuronal death or dysfunction in the rat hippocampus at concentrations of 10-120 mg/L NaF in drinking water (Basha et al 2011;Chen et al 2018a;Sharma et al 2018a;Shashi and Kumar 2016;Teng et al 2018;Wang et al 2018;Yan et al 2016;Zhao et al 2019), an influence on neurotransmitter signaling (Dong et al 2017;Sun et al 2018), and induction of oxidative stress in the brain (Bartos et al 2018;Dong et al 2017). Further studies also reported stimulation of microglia following fluoride exposure (Shuhua et al 2012;Yan et al 2013Yan et al , 2016Yang et al 2018).…”
Section: Neurobehavioral Studies and Neurotoxicitymentioning
confidence: 92%